Why Greatness Cannot Be Planned: The Myth of the Objective - Stanley, Kenneth O.; Lehman, Joel (Springer, 2015)
Why does modern life revolve around objectives? From how science is fu nded, to improving how children are educated – and nearly everything i n-between – our society has become obsessed with a seductive illusion: that greatness results from doggedly measuring improvement in the rel entless pursuit of an ambitious goal. In Why Greatness Cannot Be Plann ed, Stanley and Lehman begin with a surprising scientific discovery in artificial intelligence that leads ultimately to the conclusion that the objective obsession has gone too far. They make the case that grea t achievement can't be bottled up into mechanical metrics; that innova tion is not driven by narrowly focused heroic effort; and that we woul d be wiser (and the outcomes better) if instead we whole-heartedly emb raced serendipitous discovery and playful creativity.Controversial at its heart, yet refreshingly provocative, this book challenges readers to consider life without a destination and discovery without a compass .